Hubungan Kecemasan Dengan Kualitas Tidur Pada Tahanan Kejaksaan Negeri Bitung - Fera Tumandung (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
Every individual who experiences a change in role in social responsibility including being a prisoner mostly experiences psychological problems, one of which is stress and the effect of stress shown is anxiety, as a result of anxiety that cannot be handled, it has an impact on disturbing individual sleep patterns. The purpose of this study was to determine the relationship between anxiety and the quality of sleep of detainees at the Bitung District Attorney's Office. This research method is observational analytic research with a Cross Sectional study design. The sample taken amounted to 45 respondents using Purposive sampling. Data collection using a questionnaire sheet. The collected data were processed using the IBM SPSS Version 23 computer. For the analysis test using Spearman Rho with a level of significance (α < 0.05). Spearman Rho statistical test obtained a value ≤ ρ = 0.001 (α <0.005). This means that Ha is accepted or there is a significant relationship between the relationship between anxiety and the quality of sleep of detainees at the Bitung District Attorney's Office. This study found a relationship between anxiety and the quality of sleep of detainees at the Bitung District Attorney's Office. Suggestions for the results of this study to all respondents to be able to control the anxiety experienced by increasing spiritual activities so that anxiety does not become a contributing factor to sleep disorders.